Effect of incarceration history on outcomes of primary care office-based buprenorphine/naloxone. - Wang, Emily A; Moore, Brent A; Sullivan, Lynn E; Fiellin, David A (Journal of general internal medicine, 2010)
Behaviors associated with opioid dependence often involve criminal activity, which can lead to incarceration. The impact of a history of incarceration on outcomes in primary care office-based buprenorphine/naloxone is not known.
Keywords: Adult; Buprenorphine; Criminals; Female; Humans; Male; Middle Aged; Naloxone; Office Visits; Opioid-Related Disorders; Primary Health Care; Socioeconomic Factors; Treatment Outcome; Young Adult